Effects of Emotional intelligence on Students Academic Performance - Aysha Khatoon; Asma Afzal; Kiran Kiran; Bakhtawar Ijaz (Newinera Publisher, 2020)
This study is to investigate the significant relationship between Emotional Intelligence and Academic Performance. This investigate was done employing a quantitative strategy additionally an essential information was collected from understudies. In other to be in line with the quantitative approach chosen for this proposition, the medium through which information will be collected from respondent. only empathy and self-motivation has stronger influence (as in seen in the mean figures, correlation and regression analysis) on the academic performance of the students of economic department. It is found that while self-awareness, emotional management and interpersonal skill has a weak influence (as seen only in the mean and correlation figures) on the academic performance of students. Thus, this study recommends that students who want to succeed in their academic pursuit should take notes of their emotions intelligence (empathy and self-motivation skills). It is important for the University of Karachi to organize seminars either semester or yearly to enable students have a better understanding to their emotions or how it influences their education and academic performance.